Digital Readiness and Competitiveness of the EU Higher Education Institutions: The COVID-19 Pandemic Impact - Grinberga Zalite, Gunta; Zvirbule, Andra (Ital Publication, 2020)
Nowadays, students expect that their university will not only provide a valuable source of practical knowledge for them, but will also be ready to offer appropriate distance learning opportunities both on a daily basis to diversify and enrich the study process experience and during global pandemic crises, which will probably be the reality of their lives in the next decades. The novelty and topicality of this study is justified by the need to assess the COVID-19 pandemic impact on the European Union higher education system and its adaptability to switch from traditional to remote study forms. The objectives of the study were: 1) to analyse the need to improve digital skills in the European Union by investigating the achievements of the Digital Economy and Society Index; 2) to assess the current digital environment of Latvian public universities and conduct an in-depth study of the digital environment of Latvia University of Life Sciences and Technologies. The research methodology is based on the desk study, social survey, comparative analysis and logical construction research methods. The results of the study revealed the digital gap that still exists between the more developed Nordic European countries and the less developed Southern and Eastern European countries. However, detailed analysis of the situation in Latvia leads to the conclusion that Latvian higher education institutions have significantly increased the amount of digital content in both external and internal communication systems and can offer competitive educational services that comply with the contemporary education requirements.